Osmotic stress signaling via protein kinases - Fujii H; Zhu JK (SPRINGER BASEL AG, 2022)
Plants face various kinds of environmental stresses, including drought, salinity, and low temperature, which cause osmotic stress. An understanding of the plant signaling pathways that respond to osmotic stress is important for both basic biology and agriculture. In this review, we summarize recent investigations concerning the SNF1-related protein kinase (SnRK) 2 kinase family, which play central roles in osmotic stress responses. SnRK2s are activated by osmotic stress, and a mutant lacking SnRK2s is hypersensitive to osmotic stress. Many questions remain about the signaling pathway upstream and downstream of SnRK2s. Because some SnRK2s also functions in the abscisic acid (ABA) signaling pathway, which has recently been well clarified, study of SnRK2s in ABA signaling can provide clues regarding their roles in osmotic stress signaling.